Posterior reversible encephalopathy syndrome in a known case of beta-thalassemia major after blood transfusion: a case presentation - Diana Hanna; Mohamad Gamal Nada; Mahmoud M. Gohary (Egyptian Pediatric Association Gazette, 2024)
Abstract Background Posterior reversible encephalopathy syndrome (PRES) is a neurotoxic condition associated with a distinctive brain imaging pattern which typically occur in some complex clinical conditions. However, the leading offender to this condition remains not clear. Case presentation We report a 6-year-old female with β-thalassemia major presenting with generalized tonic–clonic convulsions, repeated attacks of projectile vomiting, blurred vision, and altered conscious level after blood transfusion. The brain magnetic resonance imaging (MRI) FLAIR sequence revealed bilateral and symmetrical subcortical edema displaying high signal intensity. Follow-up MRI 1 month later showed complete resolution of the previously identified findings. The clinical presentation along with neuroimaging pattern as well as the reversible course indicated PRES as the most suitable diagnosis. Although PRES has been previously described in different clinical settings, this is a rare case of PRES recognized after blood transfusion in a child with β-thalassemia major. Conclusion Acute neurological symptoms in children with thalassemia should raise high suspicion for PRES, especially after blood transfusion.